2019
DOI: 10.1002/ppul.24490
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term outcome of an isolated vascular ring – A single‐center experience

Abstract: Background and Objectives The aim of this study is to document the long‐term outcome of patients with a vascular ring. Methods A single‐center retrospective review of clinical symptoms was conducted in all patients born between 1980 and 2013, diagnosed with a complete vascular ring and at least 2 years of follow‐up. Data were extracted from patient files and clinical symptoms were assessed by questionnaires sent to the parents. Age and diagnostic tools, type of surgery, postoperative complications, and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Nine patients complained of persistent respiratory symptoms, mostly cough, dyspnea, and/or wheezing with abnormal spirometry and/or lung volumes in seven subjects. Depypere et al 7 proposed that residual symptoms could be a risk for the development of exercise‐induced wheezing. In our study, none of the patients had postexercise bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine patients complained of persistent respiratory symptoms, mostly cough, dyspnea, and/or wheezing with abnormal spirometry and/or lung volumes in seven subjects. Depypere et al 7 proposed that residual symptoms could be a risk for the development of exercise‐induced wheezing. In our study, none of the patients had postexercise bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…The operation is considered safe with low rates of complications 4 and clinical improvement appears in the vast majority of children. [5][6][7] Clinical follow-up (ranging from 1 year to 34 years) showed that 16%−68% of patients were symptom-free. 4,8 Double aortic arch patients were found to have an increased risk of remaining symptomatic 8,9 with lessened improvement with associated tracheomalacia.…”
mentioning
confidence: 99%
“…Due to the sporadic nature of this anomaly, there is not enough data on the long-term prognosis or possible complications during endovascular procedures. 58…”
Section: Cervical Aortic Archmentioning
confidence: 99%
“…Depypere et al 19 reported single-center experience of 51 children with an isolated vascular ring with a median follow-up of 8 years.…”
Section: Anatomic Lung Airway and Vascular Malformationsmentioning
confidence: 99%
“…As with CLM, these lesions are being detected prenatally with increasing frequency, raising the question of when and whether to intervene surgically in asymptomatic or mildly symptomatic cases. Depypere et al 19 reported single‐center experience of 51 children with an isolated vascular ring with a median follow‐up of 8 years. Most were diagnosed before 2 years of age and all patients with double aortic arch were symptomatic on presentation.…”
Section: Introductionmentioning
confidence: 99%